1979
DOI: 10.1029/gl006i001p00021
|View full text |Cite
|
Sign up to set email alerts
|

Polar cap electric field structures with a northward interplanetary magnetic field

Abstract: Polar cap electric fields patterns are presented from times when the S3‐2 Satellite was near the dawn‐dusk meridian and IMF data were available. With Bz ≥ 0.7 γ, two characteristic types of electric field patterns were measured in the polar cap. In the sunlit polar cap the convection pattern usually consisted of four cells. Two of the cells were confined to the polar cap with sunward convection in the central portion of the cap. The other pair of cells were marked by anti‐sunward flow along the flanks of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
160
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 316 publications
(173 citation statements)
references
References 7 publications
13
160
0
Order By: Relevance
“…In this picture, plasma at the footprint of the reconnection X-line convects sunward, due to the magnetic tension of the newly-reconnected field lines, before being swept antisunward towards dawn and dusk with the magnetosheath flow. Early observations of ionospheric flow during northward IMF conditions showed the existence of sunward convection within the polar cap ionosphere (Maezawa, 1976;Burke et al, 1979). Further observations illustrated that "four-cell" convection was typical during these conditionstwo reverse convection cells within the polar cap, with two "normal" convection cells, thought to be driven by viscous processes at the magnetopause, at lower latitudes (Heelis et al, 1986;Knipp et al, 1991;Freeman et al, 1993;Reiff and Heelis, 1994;Cumnock et al, 1995).…”
Section: Introductionmentioning
confidence: 95%
“…In this picture, plasma at the footprint of the reconnection X-line convects sunward, due to the magnetic tension of the newly-reconnected field lines, before being swept antisunward towards dawn and dusk with the magnetosheath flow. Early observations of ionospheric flow during northward IMF conditions showed the existence of sunward convection within the polar cap ionosphere (Maezawa, 1976;Burke et al, 1979). Further observations illustrated that "four-cell" convection was typical during these conditionstwo reverse convection cells within the polar cap, with two "normal" convection cells, thought to be driven by viscous processes at the magnetopause, at lower latitudes (Heelis et al, 1986;Knipp et al, 1991;Freeman et al, 1993;Reiff and Heelis, 1994;Cumnock et al, 1995).…”
Section: Introductionmentioning
confidence: 95%
“…Whereas the morphology of ionospheric convection during intervals dominated by southward IMF was well established before the SuperDARN era, there was disagreement over the form of ionospheric convection during intervals of strongly northward IMF. Early studies (Burke et al 1979;Reiff and Burch 1985) suggested the existence of four convection cells during northward IMF conditions-two ''reverse'' cells at high-latitudes driven by lobe reconnection antisunward of the cusp regions, and two ''normal'' cells at lower latitudes driven by viscous processes at the magnetopause. However, Heppner and Maynard (1987) argued that there might not be four convection cells but only two, highly distorted cells.…”
Section: The Structure Of Global Convectionmentioning
confidence: 99%
“…The two merged ends with both feet in the solar wind simply blow away through the magnetosheath [Maezawa, 1976]. For the described interplanetary conditions a lobe cell is embedded within the convection cell [Burke et al, 1994]. Crooker and Rich [1993] showed that the ionosphere with the embedded lobe cell is favored to be in the summer hemisphere and has larger potential drops than the corresponding winter hemisphere convection cell.…”
mentioning
confidence: 99%